Large-Scale Production of Intermediate-Purity, Soluble Human Plasminogen - Bergström, K; Tse, Ann O.; Johnson, A. J (Thrombosis and Haemostasis, 1971)
A method is described for laboratory, pilot or large-scale production of intermediatepurity human plasminogen soluble at neutral pH, with a specific proteolytic activity of approximately 12.5 CTA units/mg protein. Batches of 100-200 g can be readily produced from Fraction III paste from outdated or fresh-frozen plasma. Since this plasminogen is stable on long-term storage, and low in spontaneous plasmin activity, it is especially useful as an assay reagent (substrate) and as starting material for the preparation of high-purity plasminogen.